Estimation of Solar Radiation on Tilted Surface by Using Regression Analysis at Different Locations in India - Qadeer, Abdul; Khan, Mohammad Emran; Alam , Shah (Distributed Generation & Alternative Energy Journal, 2020)
This study is to find the regression model for estimation of monthly mean hourly global solar radiation on tilted surface at different locations of India. This study is quite precious due to lack of solar radiation data availability on the tilted surface. Firstly, we have selected some locations having different climatic conditions such as New Delhi, Mumbai, Kolkata, Lucknow and Jaipur to find the solar radiation on tilted surface using Liu and Jordan model, HDKR model and Perez model. The mean values of these models are plotted along with the daytime. Based on regression techniques, four empirical models are developed which are tested to compute the solar radiation on tilted surface for three new stations Ahmadabad, Bangalore and Chennai. The estimated solar radiation by these four developed models are compared with the estimated values using existing models Lie & Jordan, HDKR and Perez based on mean bias error (MBE) and root mean square error (RMSE). It has been found that developed Model-3 has minimum error and the values estimated this model is comparable to existing models. The maximum values of RMSE in Model-3 in tested stations are 2.01% with Liu and Jordan, 2.63% with HDKR and 2.10% with Perez. Similarly, maximum values of MBE are −1.79% with Liu and Jordan, −2.27% with HDKR and −1.89% with Perez. Now the Model-3 finally selected to determine the solar radiation on Bhopal, Bhubneshwar, Dehradun, Guwahati and Trivendrum (Thiruvananthapuram).